Gaya Bahasa Pada Pengajian Gus Iqdam: Kajian Semantik - Agustin Yuslia Hasti Ananta; Erwan Kustriyono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to identify the language style used by Gus Iqdam. The method used in this research is a qualitative research method. This research data was taken from Gus Iqdam’s lecture video uploaded on the YouTube channel. The techniques used in collecting data are listening techniques, note takin techniques and documentation techniques. The results of this research found that the language style used by Gus Iqdam in his lectures had its own characteristics and uniqueness. This uniqueness can be seen from Gus Iqdam’s choice of words, intonation and the way he relates religious teachings to everyday life. This uniqueness makes Gus Iqdam’s lectures easy for his congregation to remember and understand. The language styles used by Gus Iqdam include parables or similes, metaphors, personification, hyperbola, litotes, antithesis, pleonasm, repetition and inuedo.